Small-scale fishing income and fuel consumption: Fiji's artisanal sea cucumber fishery. (27th March 2018) - Purcell, Steven W; Lalavanua, Watisoni; Cullis, Brian R; Cocks, Nicole
Abstract: Understanding the income and costs of fishing is fundamental to managing fisheries and planning interventions to improve efficiency and gender equity. Few studies offer data on fisher incomes and fuel use in small-scale fisheries (SSFs), and fewer have assessed factors influencing variation among fishers and between genders. We interviewed 235 artisanal fishers among 34 island villages in an artisanal sea cucumber fishery in Fiji. Linear mixed models were used to determine the effect of geographic and socioeconomic variables on incomes and fuel use from fishing sea cucumbers. Net income of sea cucumbers to fishers, averaging FJ$8, 171 year −1 (US$4, 494 year −1 ) (range: FJ$0–52, 008 year −1 ), varied among villages and was 47% lower for women than men. On an average, 60% of fishers' gross annual income came from fishing and selling sea cucumbers, although this proportion varied greatly even within villages. Fishers who practised gleaning, fished less often, or possessing numerous livelihood income streams, were less economically dependent on sea cucumbers. Men tended to estimate higher incomes for an average day of fishing than women when compared with their recall of last sale. Fuel use varied greatly among regions in Fiji but, overall, averaged 428 L fisher −1  year −1, and represented 28% of gross income. More economical fishing strategies by women resulted in lower fuel use than men per fishing day. Breath-hold divers used less fuel (compared to fishers using scuba) and fishers targeting deep-water species used more fuel than other fishers. A best approximation of 8000 t CO2 year −1 for the carbon footprint of the whole fishery suggests that some SSFs, such as the one studied here, can be significant contributors to greenhouse gas emissions, even compared to many large-scale fisheries globally. Reforms to the management of SSFs should consider regulations that minimize carbon emissions and reduce economic dependency on vulnerable marine resources.